Intestinal stem cells and their niches in homeostasis and disease - Zhou, Jun; Boutros, Michael (Cells & development, 2023)
Tissues such as the intestine harbor stem cells that have remarkable functional plasticity in response to a dynamic environment. To adapt to the environment, stem cells constantly receive information from their surrounding microenvironment (also called the ‘niche’) that instructs them how to adapt to changes. The Drosophila midgut shows morphological and functional similarities to the mammalian small intestine and has been a useful model system to study signaling events in stem cells and tissue homeostasis. In this review, we summarize the current understanding of the Drosophila midgut regarding how stem cells communicate with microenvironmental niches including enteroblasts, enterocytes, enteroendocrine cells and visceral muscles to coordinate tissue regeneration and homeostasis. In addition, distant cells such as hemocytes or tracheal cells have been shown to interact with stem cells and influence the development of intestinal diseases. We discuss the contribution of stem cell niches in driving or counteracting disease progression, and review conceptual advances derived from the Drosophila intestine as a model for stem cell biology.